Analysis of Financial Performance and Capital Structure on Company Value with Good Corporate Governance (Board Diversity) as a Moderating Variable in the Healthcare Sector for the Period 2019-2023 - Septiana Galuh Rahmawati; Sri Murdiati; Yuni Utami (Countable (Contemporary Business and Sustainability Science), 2025)
This study aims to determine and analyze Financial Performance and Capital Structure on Company Value with Good Corporate Governance (Board Diversity) as a Moderating Variable in the Healthcare Sector for the 2021-2023 Period. Financial performance is measured by Return on Assets (ROA), capital structure is measured by Debt to Equity Ratio (DER), Company value is measured using Tobin's Q and Good Corporate Governance (GCG) using the proportion of female board of directors. In this context, Good Corporate Governance (GCG) is used as a moderating variable to see how company value can affect the relationship between Financial Performance and capital structure. Type of research used quantitative, the data used is secondary data obtained from published financial reports on the Indonesia Stock Exchange (IDX) in 2019-2023. The population in this study was 33 companies and the research sample was 13 company samples. The data analysis method uses multiple linear regression analysis with Moderated Regression Analysis (MRA). To test the hypothesis using a tool, namely the SPSS 22 program. The results of this study indicate that financial performance does not affect the value of the company. Capital structure has a positive effect on the value of the company. Good Corporate Governance (GCG) is not able to moderate the influence between financial performance on the value of the company. And Good Corporate Governance (GCG) is able to moderate the influence between capital structure on the value of the company.